Interesting issues for an industry at a time of record growth - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2014)
This editorial notes several key indicators of record growth in Australian telecommunications, as the backdrop to the second issue of this multidisciplinary policy Journal. The growth in social connectivity and ‘big data’, together with the rapid evolution of new infrastructure technologies, all pose interesting challenges for good policy making — and for keeping up with new developments. The satisfying backdrop of high growth in the telecommunications industry provides a canvas on which to introduce the other thirteen articles which make up this edition (V2 N1) of the Journal of Telecommunications and the Digital Economy.